Effect of mixed liquor volatile suspended solids on membrane Fouling during short and long-term operation of membrane bioreactor (2014)
The aim of this study was to examine the impact of different Mixed Liquor Volatile Suspended Solids (MLVSS) concentrations on membrane fouling, in a submerged Membrane Bioreactor (MBR) at short and long-term MBR operation for wastewater treatment -- Three laboratory-scale in a submerged MBR system were operated under critical flux, sub-critical flux, and an intermittent suction time and backwashing conditions -- At shortterm MBR operation with mixed liquors of 4,200 and 6,150 mg MLVSS L-1, the hydraulic resistance of membranes followed a same trajectory with averages of 5.0E+12 m-1, whereas for 7,940 mg MLVSS L-1, a high resistance of up to 1.7E+13 m-1 was obtained -- The result showed that high biomass concentrations decreased to permeability due to a bio-layer formed in the membrane surface and high Extracellular Polymeric Substance (EPS)